Spintronic Terahertz Emission in Ultrawide Bandgap Semiconductor/Ferromagnet Heterostructures. Issue 1 (31st October 2022) - Comstock, Andrew; Biliroglu, Melike; Seyitliyev, Dovletgeldi; McConnell, Aeron; Vetter, Eric; Reddy, Pramod; Kirste, Ronny; Szymanski, Dennis; Sitar, Zlatko; Collazo, Ramón; Gundogdu, Kenan; Sun, Dali
Abstract: Recent successful integration of semiconductors into spintronic THz emitters has demonstrated a new pathway of control over terahertz (THz) radiation through ultrafast demagnetization dynamics. Here, the spintronic THz emission from different ultrawide bandgap (UWBG) semiconductors interfaced with ferromagnets is studied. The authors show that the Schottky barrier in the UWBG semiconductor AlN acts as a spin filter that increases the polarization of the spin current injected from the ferromagnet. Furthermore, the authors show that the two‐dimensional electron gas at the interface between Al0.25 Ga0.75 N and GaN enhances the magnitude of the emitted radiation due to the high spin‐to‐charge conversion efficiency induced by the Rashba effect that results in a hallmark asymmetry in emission amplitude. The results provide a framework for future engineering of semiconducting/ferromagnet heterostructures for ultrafast communications technologies beyond 5G. Abstract : This work investigates spintronic THz emission from ultrawide bandgap (UWBG) semiconductors interfaced with ferromagnets. UWBG semiconductors act as a spin filter that increases the spin injection efficiency at the interface caused by the large bandgap, resulting in an enhancement of the THz amplitude.